Republic of Latvia : First Review and Financing Assurances Review Under the Stand By Arrangement, Requests for Waivers of Nonobservance of Performance Criteria, and Rephasing of Purchases Under the Arrangement. (IMF Staff Country Reports; Country Report ;, 2009)
The Latvian authorities have strengthened their intervention capacity, financial supervision, and monitoring framework, and have taken steps to contain risks in Parex Bank. The staff report reviews the Republic of Latvia's economic developments and policies. Substantial progress has been achieved in stabilizing the financial sector. The collapse in output has revealed significant underlying fiscal weaknesses that risk leading to unsustainable deficits in the absence of strong corrective measures. The deeper downturn is also in part explained by the much worse-than-projected international environment.